Aquatic plants : pharmaceutical and cosmetic applications - Lall, Namrita (Boca Raton, FL : CRC Press, 2021)
"Aquatic Plants: Pharmaceutical and Cosmetic Applications provides a concise description of popular aquatic plants found across the globe. This beautifully illustrated book explains aquatic plants' distribution, ethnobotanical uses, genome sequencing, chemical compounds and biological activity as well as their sustainable production"--
An introduction to aquatic plants -- Aquatic plants native to Africa -- Aquatic Plants Native to Asia and Australia -- Aquatic Plants Native to America -- Aquatic plants native to Europe -- Sustainable Production of Aquatic and Wetland Plants.
OCLC-licensed vendor bibliographic record.
Keywords: Aquatic plants; HEALTH & FITNESS / Herbal Medications; SCIENCE / Life Sciences / Botany; SCIENCE / Chemistry / General